World meat consumption patterns: An overview of the last fifty years (1961–2011). (November 2015) - Sans, P.; Combris, P.
Abstract: Driven by economic development and urbanisation, animal-based protein (ABP) consumption has surged worldwide over the last 50 years, rising from 61 g per person per day in 1961 to 80 g per person per day in 2011. This contribution analyses the apparent convergence of dietary models worldwide with respect to the proportion of ABP and especially meat in intake. By using FAO data for 183 countries over the period 1961–2011, the authors show the connection between annual per capita GDP and the level of ABP (R2 = 0.62) and meat consumption (R2 = 0.62). They emphasise the surge in ABP intake in emerging countries (China, Brazil) which has partly replaced plant protein. However, for similar degrees of economic development, the composition of ABPs and the position of meat within this category vary significantly among countries, suggesting that historical, geographical, cultural and religious factors may be involved. Highlights: Animal-based protein (ABP) consumption has surged worldwide over the last 50 years. Composition of ABPs and position of meat within this category vary among countries. Economic development and urbanisation are two main drivers of meat consumption.